Colombia Mercury Inventory 2011 (2012)
In the ancient Andes, mercury was mined, retorted, and used for small-scale gold production and cinnabar was used as a part of funeral rites.  Colombia's most well-known mercury mine, Mina La Esperanza (Dept. Caldas), closed in the 1960s and now, mercury is acknowledged as a global contaminant by the US Environmental Protection Agency, the US State Department, the United Nations Environmental Program, and many other organizations.  Colombia is considered to be one of the top three users of mercury in the world.  The government of Colombia is concerned about environmental contamination from mercury releases and has attempted to reduce the use of mercury for small-scale gold mining from140 t/yr to70 t/yr.  The United Nations Industrial Development Organization (UNIDO) planned to invest $US1.7 million dollars to help reduce the use of mercury in Colombia.  In 2011, Colombia imported mercury from Mexico (23 t) and Spain (21 t) and the mercury was used for small-scale gold mining, chlor-alkali production, and neon lighting.  In Remedios, north-central Colombia, and Chocó, western Colombia, alluvial gold (gold-silver-platinum) is being produced by mercury as well as non-mercury or "green-gold" methods.  Many of the gold shops where the gold-mercury amalgam is burned have water traps to capture the mercury that is volatilized when the amalgam is burned.  In Remedios, simple ball-mills, or entables, also use mercury to amalgamate the fine-grained alluvial gold before burning.  Collaboration with Japanese researchers and the efforts of Universidad Nacional de Colombia scientists in Medellín has resulted in reduction in the use of mercury at intermediate-sized gold mines in Depts. Nariño and Antioquia, respectively.  In Dept. Chocó, western Colombia, the use of mercury with dredges and sluices, which also cause increased sediment load in the rivers, has decreased.  There is one mercury-cell chlor-alkali plant in Colombia and mercury is also imported in fluorescent and CFLs, dental amalgam capsules, thermometers, batteries, light-up kid's shoes and toys; however, no mercury is recycled.  Some mercury-containing material may be encapsulated and then placed in landfills.  Gold from the small-scale mines has been used to fund guerilla and paramilitary activities.  Increased gold prices, to $US1,600 per troy ounce, continue to drive the use of mercury despite the increased mercury prices, to $US3,000 per 34.5 kg flask. Key words: mercury, gold, green gold, environment, retorting, amalgamation